Antioxidant and mutagenic activity of herbal tea prepared from Cosmos caudatus leaves at different maturity stages - Dian-Nashiela Fatanah,; Noriham Abdullah,; Nooraain Hashim,; Azizah Abd. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Different maturity stages of Cosmos caudatus leaves have been used to prepare herbal tea were investigated for their effect on antioxidant activity and mutagenic activity. The analyses carried out were total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), 2-2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, β-carotene bleaching assay, oxygen radical absorbance capacity (ORAC) and Ames Salmonella mutagenicity. The results demonstrated that, C. caudatus herbal tea prepared from young leaves showed significantly highest antioxidant activity for all assays tested, followed by mixed leaves, mature leaves, old leaves and the lowest was in C. caudatus herbal tea from a commercial brand. Pearson’s correlation coefficient also demonstrated that TPC and TFC displayed a strong correlation with all antioxidant activity assays, showing that these compounds were the major contributors to the antioxidant activity in C. caudatus herbal tea. However, all studied C. caudatus herbal tea showed no mutagenic effects against Salmonella typhimurium tester strain TA98 and TA100 with and without S9 metabolic activation. Hence, it can be concluded that, different maturity stages could affect the antioxidant activity in C. caudatus herbal tea as it reduced the antioxidant activity as maturity increased, but did not give any effect on the mutagenic activity.